2020
DOI: 10.1038/s41401-020-00503-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug development in targeting ion channels for brain edema

Abstract: Cerebral edema is a pathological hallmark of various central nervous system (CNS) insults, including traumatic brain injury (TBI) and excitotoxic injury such as stroke. Due to the rigidity of the skull, edema-induced increase of intracranial fluid significantly complicates severe CNS injuries by raising intracranial pressure and compromising perfusion. Mortality due to cerebral edema is high. With mortality rates up to 80% in severe cases of stroke, it is the leading cause of death within the first week. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 251 publications
(395 reference statements)
0
29
0
Order By: Relevance
“…Under stroke conditions, neuroinflammation can disrupt the BBB, whereby blood infiltrates the brain matter to induce vascular edema (Yang et al, 2019). Specifically, cerebrovascular edema caused by acute ischemic stroke and traumatic brain injury (TBI) further exacerbates BBB dysfunction by disrupting the balance between transporter and ion channels (Luo et al, 2020). In mouse models of transient middle cerebral artery occlusion, the AQP4 expression level in astrocytes was rapidly up-regulated following stroke and correlated with the degree of edema over time (Ribeiro Mde et al, 2006).…”
Section: Permeability Of the Blood-brain Barrier Affects The Brain Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Under stroke conditions, neuroinflammation can disrupt the BBB, whereby blood infiltrates the brain matter to induce vascular edema (Yang et al, 2019). Specifically, cerebrovascular edema caused by acute ischemic stroke and traumatic brain injury (TBI) further exacerbates BBB dysfunction by disrupting the balance between transporter and ion channels (Luo et al, 2020). In mouse models of transient middle cerebral artery occlusion, the AQP4 expression level in astrocytes was rapidly up-regulated following stroke and correlated with the degree of edema over time (Ribeiro Mde et al, 2006).…”
Section: Permeability Of the Blood-brain Barrier Affects The Brain Microenvironmentmentioning
confidence: 99%
“…On the other hand, AQP4 knockout in mice revealed intact BBB structure, which resulted in significantly reduced mortality, infarction, and cerebral edema after stroke as well as improvement in long-term neurobehavioral performance (Manley et al, 2000;Yao et al, 2015). Moreover, the sulfonylurea receptor 1 (SUR1)-transient receptor potential melastatin 4 (TRPM4) pathway is closely associated with cerebral edema formation, and conversely, SUR1-TRPM4 inhibitors reduce brain swelling and improve clinical outcomes following acute ischemic stroke or TBI (Luo et al, 2020). In addition, recent research has demonstrated that SUR1-TRPM4 and AQP4 form a novel heterooligomer that amplifies ion/water osmotic coupling and drives astrocyte swelling (Stokum et al, 2018), which coordinate to affect brain edema.…”
Section: Permeability Of the Blood-brain Barrier Affects The Brain Microenvironmentmentioning
confidence: 99%
“…TRPM4 is Ca 2+ activated, and is one of only two known ion channels in the mammalian genome that exclusively and non-selectively conducts monovalent cations [ 5 , 58 ]. TRPM4 is an independently functional ion channel, whereas SUR1 requires binding to a pore-forming subunit for functional capability [ 59 , 60 ].…”
Section: Sur1-trpm4mentioning
confidence: 99%
“…Moreover, TRPM4 knockout mice show a variety of deficits in hippocampus-related behavioral tasks linked to decreased LTP ( Bovet-Carmona et al, 2018 , 2019 ). TRPM4 is also involved in neuronal degeneration and ischemia/reperfusion damage ( Schattling et al, 2012 ; Leiva-Salcedo et al, 2017 ), where it plays a key role in oncotic cell swelling and neuronal death, leading to the proposal that TRPM4 inhibition could be a treatment for these conditions ( Jha et al, 2020 ; Luo et al, 2020 ; Robert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%